البعد الابستيمولوجي في الدرس الأدبي المقارن - صابرين, عدة (كلية الأدب العربي والفنون, 2024)
هذه الدّراسة تتناول استكشاف جهود المفكر المقارن المغربيّ سعيد علّوش الذي يعتبر من الرواد في مجال دراسة الأدب المقارن في النقد العربيّ، حيث اعتمد في دراسته إلى مختلف الأبعاد التي انتهجها في دراسته المقارناتيّة This study deals with exploring the efforts of the Moroccan comparative thinker Said Alloush, who is considered one of the pioneers in the field of studying comparative literature in Arabic criticism, as he relied in his study on the various dimensions that he followed in his comparative study.
جهود سعيد علوش أنموذجا
Keywords: البعد الإبستمولوجي، الأدب المقارن، سعيد علّوش; epistemological dimension, comparative literature, SaeedAlloush.